2022
DOI: 10.3390/f13081242
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Compounds Profile Present in the Selected Wood Rot

Abstract: Wood rot fungi are an essential link in the forest ecosystem. The presented study aimed to determine the content of selected antioxidant active compounds of selected saprobionts commonly found in the European forests: Hypholoma fasciculare (Huds.) P. Kumm, Bjerkandera adusta (Willd.) P. Karst., Inonotus obliquus (Fr.) Pilát, Kuehneromyces mutabilis (Schaeff.) Singer & AH Sm., Trametes versicolor (L.) Lloyd, Pleurotus ostreatus (Jacq.) P. Kumm., Pholiota squarrosa (Vahl) P. Kumm. Chemical methods (HPLC dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
3
1
Order By: Relevance
“…Phenolic compounds are well known for their free radical inhibition, metal inactivation, prevention of negative reactivity of undesired reactive oxygen, peroxide decomposition, and oxidative disease burden [41,42]. The flavonoid content found in T. versicolor collected from Turkey (13.82 ± 0.2 mg QE/mg) [29] and Himachal Pradesh, India (13.13 mg QE/mg) [40] fell within the range observed in the current study (9.02 ± 0.64-14.01 ± 1.00 mg QE/mg), whereas Szwajkowska-Michałek et al [43] found poor flavonoid content in T. versicolor collected from Poland, and Pop et al [44] failed to identify any flavonoid content. Flavonoids can help reduce blood platelet aggregation, lipoprotein oxidation, and cardiovascular mortality, and can regulate vascular reactivity [45].…”
Section: Results Of Analysis Of Biochemical Constituents In Turkey Ta...supporting
confidence: 74%
See 1 more Smart Citation
“…Phenolic compounds are well known for their free radical inhibition, metal inactivation, prevention of negative reactivity of undesired reactive oxygen, peroxide decomposition, and oxidative disease burden [41,42]. The flavonoid content found in T. versicolor collected from Turkey (13.82 ± 0.2 mg QE/mg) [29] and Himachal Pradesh, India (13.13 mg QE/mg) [40] fell within the range observed in the current study (9.02 ± 0.64-14.01 ± 1.00 mg QE/mg), whereas Szwajkowska-Michałek et al [43] found poor flavonoid content in T. versicolor collected from Poland, and Pop et al [44] failed to identify any flavonoid content. Flavonoids can help reduce blood platelet aggregation, lipoprotein oxidation, and cardiovascular mortality, and can regulate vascular reactivity [45].…”
Section: Results Of Analysis Of Biochemical Constituents In Turkey Ta...supporting
confidence: 74%
“…The inhibition of cancer cell growth, modulation of immune function, and prevention of DNA, lipid, and protein oxidative damage could all be achieved with lycopene-rich products [46][47][48]. The β-carotene content in T. versicolor collected from Poland in a previous study was reported to be 1.01 mg/g [43], which is higher than the range observed in the present study (0.31-0.72 mg/g). It has been reported that both lycopene and β-carotene can stabilize or inhibit oxidation reactions [49].…”
Section: Results Of Analysis Of Biochemical Constituents In Turkey Ta...contrasting
confidence: 50%
“…Surprisingly, in the case of an equimolar mixture of the substrates, the bioluminescence spectra for hsPKS corresponded to only coumaric acid, while nnHispS corresponded to only caffeic acid ( Figure 4 D). This result suggests the preference of hsPKS for coumaric over caffeic acid for the synthesis of hispidin-like compounds, and is interesting in the context of the availability of these substrates in fungal cells, as a related Hypholoma species showed up to a 3-fold greater concentration of both ferulic and coumaric acids than caffeic acid [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Assay retention times for acids were as follows: kaempferol 6.11 min, gallic 8.85 min, vanillic 9.71 min, luteolin 11.89 min, protocatechuic 12.23 min, vanillin 14.19 min, apigenin 16.43 min, catechin 18.09 min, 4‐hydroxybenzoic 19.46 min, chlorogenic 21.56 min, caffeic 26.19 min, syringic 28.05 min, naringenin 31.22 min, vitexin 35.41 min, rutin 38.11 min, quercetin 39.58 min, p‐coumaric acid 40.20 min, ferulic acid 46.20 min, sinapic acid 48.00 min, and t‐cinnamic acid 52.40 min, respectively. Recovery rates for the analysed phenolic compounds were as follows: kaempferol 86 ± 5.3%, gallic acid 92 ± 4.4%, vanillic 79 ± 8.5%, luteolin 96 ± 2.7%, protocatechuic acid 90 ± 4.8%, vanillin acid 88 ± 5.1%, apigenin 93 ± 3.8%, catechin 89 ± 5.7%, 4‐hydroxybenzoic acid 96 ± 3.78%, chlorogenic acid 92 ± 2.8%, caffeic acid 86 ± 6.7%, syringic acid 94 ± 3.9%, naringenin 88 ± 4.8%, vitexin 95 ± 3.8%, rutin 93 ± 4.9%, quercetin 97 ± 1.9%, p‐coumaric acid 89 ± 3.6%, ferulic acid 91 ± 4.9%, sinapic acid 94 ± 5.1%, and t‐cinnamic acid 97 ± 2.9% (Stuper‐Szablewska et al., 2023; Szwajkowska‐Michałek et al., 2022). Three replicates of averaged pine needle samples from one location were analysed.…”
Section: Methodsmentioning
confidence: 99%